Comorbidity of inflammatory bowel disease with atypical hemolytic uremic syndrome in pediatric patients - Shin, H. Stella (Clin Nephrol Case Stud, 2019)
Atypical hemolytic uremic syndrome (aHUS) is a form of thrombotic microangiopathy mediated by dysregulation of the alternative complement pathway. Complement-amplifying conditions such as respiratory and gastrointestinal infections, pregnancy, malignancy, and systemic autoimmune diseases such as systemic lupus erythematosus have been associated with the clinical manifestation of aHUS. Inflammation of the gastrointestinal tract is a potent stimulus for complement activation, and we describe a series of three pediatric patients with aHUS and comorbidity of inflammatory bowel disease (IBD). In two of the three cases, the diagnosis of aHUS preceded the diagnosis of IBD, perhaps suggesting a mechanistic link between complement dysregulation and thrombotic microangiopathy in the gastrointestinal tract and the ensuing inflammatory changes of IBD.